Application of Al-Quran Murottal Therapy to Reduce Pain Scale in Osteoarthritis Post Total Knee Replacement (TKR) Dextra Operation in the Eri Soedewo Pavilion Room, 5th Floor, Gatot Soebroto Army Hospital - Hayati, Teti; Fauzia, Wilda (JOURNAL EDUCATIONAL OF NURSING(JEN), 2022)
Osteoarthritis is the most common inflammatory joint disease. Based on the World Health Organization (WHO) in 2017, it is estimated that OA sufferers in the world reached 9.6% in men and 18% in women. (Budiman & Widjaja, 2020). Objective: To obtain an overview of nursing care for Mr. M with post-operative Total Knee Replacement (TKR) to overcome pain by implementing classical music therapy. The method used during the study was descriptive in the form of a case study that studied a nursing care problem in patients with osteoarthritis on the 5th Floor of the Eri Soedewo Pavilion, Gatot Soebroto Army Hospital. The results of the case study conducted for 3 days showed that the provision of Al-Qur'an murrottal therapy was quite significant in reducing pain in post-operative patients. The conclusion obtained was that after the results of the case study, it could be concluded that the provision of post-operative murrottal therapy for Total Knee Replacement had an effect on reducing pain in osteoarthritis patients.